The inclusion of LGBTQ + people within UK health policy: a critical discourse analysis - Debbie Braybrook; William E. Rosa; Charlotte Norman; Richard Harding; Katherine Bristowe (International Journal for Equity in Health)
Abstract Background Health policymakers can leverage change to improve equity in access to care, patient experiences and clinical outcomes. Despite legal progress to reduce health inequalities, social and systemic injustices persist and lesbian, gay, bisexual, trans and queer (LGBTQ+) people have increased risk of some health conditions and poorer health outcomes linked to the discrimination they experience. In 2022, 42 regional integrated care systems were created across England to reduce health inequalities and improve the wellbeing of their local population. Methods This study aimed to examine the inclusion of UK Equality Act (2010) protected characteristics within the 42 publicly available integrated care system strategies, and to consider specifically how LGBTQ + communities and their needs, experiences and outcomes are framed within these strategies. A Critical Discourse Analysis was conducted positioned within a social constructivist paradigm. Results Almost all strategies talked about the needs of their populations in terms of age (42/42), disability (42/42), gender (41/42), ethnicity (39/42) and maternity or pregnancy (39/32). 27/42 strategies mentioned religion. There were no references to marital status. 22/42 strategies referred to LGBTQ + people, but only around 25% of those references provided context about the specific needs of LGBTQ + people, the health inequities they face, or services for LGBTQ + people. Regarding gender minorities, there were eight mentions of trans people and no mentions of intersex people, despite some policies using the acronym LGBQTI. While there were two mentions of inequities in care delivery for trans people, the specific health or social care needs of trans people were not described in any strategies, and there were a small number of examples where trans people were presented in a problematizing frame; with no discussion of trans inclusive care, only problems associated with being trans. Across all 42 strategies there were only four references to systemic forces (e.g. homophobia, transphobia, discrimination) affecting LGBTQ + people. Conclusions While the needs of some minoritized groups are well recognized within health policies, LGBTQ + people remain marginalized. Further work is needed to educate and enable policy makers to advocate for LGBTQ + people and communities, and to ensure equitable and respectful inclusion of all minoritised groups.